2005
DOI: 10.1002/macp.200500045
|View full text |Cite
|
Sign up to set email alerts
|

Design and Properties of Degradable Networks Based on Free Radical Copolymerization of Poly(1,3‐dioxolane) Macromonomers with Hydrophobic or Hydrophilic Comonomers in Water

Abstract: Summary: Potentially degradable amphiphilic or hydrophilic copolymeric networks were synthesized directly in water by free radical copolymerization of α, ω‐poly(1,3‐dioxolane) (PDXL) macromonomers with vinyl monomers such as methyl methacrylate, butyl methacrylate, styrene or 2‐hydroxyethyl methacrylate. Since PDXL macromonomers behave typically as amphiphiles, the rates of copolymerizations with hydrophobic comonomers are much higher than those of similar reactions carried out in organic solvents. Therefore c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Numerous methods have been developed to synthesize cross‐linked polymeric networks 1, 2. These methods can be classified into three groups: methods involving free radical copolymerization of two monomers,3 including macromonomers,4 methods employing formation of bridges between existing linear or branched chains by vulcanization, peroxidation, or irradiation,5, 6 and those based on chemical reactions involving bifunctional polymers bearing living anionic or other functions at the chain ends 7–9. In the last method, the average length of the precursor polymer can be chosen arbitrarily, and determined precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods have been developed to synthesize cross‐linked polymeric networks 1, 2. These methods can be classified into three groups: methods involving free radical copolymerization of two monomers,3 including macromonomers,4 methods employing formation of bridges between existing linear or branched chains by vulcanization, peroxidation, or irradiation,5, 6 and those based on chemical reactions involving bifunctional polymers bearing living anionic or other functions at the chain ends 7–9. In the last method, the average length of the precursor polymer can be chosen arbitrarily, and determined precisely.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many multivariate hydrogels, which can overcome the defects in the properties of unitary hydrogels, had been designed and prepared with special monomers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] As we know, PNIPA hydrogel belongs to nonionic hydrogel and is a typical temperature-sensitivity hydrogel. Because there is no hydrophilic group in the structure, the SR of PNIPA hydrogel is very low, which limits the application of PNIPA hydrogel in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…For example, hydrogels are used as drug delivery matrices and tissue engineering scaffolds with high performance designed by a controlled network structure and combination with various kinds of polymers. By incorporating a degradable linkage into gels, we can claim more variety of application of the gels as materials programmed for degradation after temporary use. The structural change and degradation of the network polymers are triggered by a stimulus such as heating, , pH, , glucose, antigen, and enzymatic activities . We recently reported that polyperoxide (PP), as a new kind of a degradable polymer, is readily produced by the radical copolymerization of 1,3-diene monomers with oxygen under mild conditions. The obtained PP includes a labile O−O bond in their main chain, leading to be readily degraded via a radical chain mechanism using stimuli such as heating, UV irradiation, and the addition of a base. , We also synthesized the PP gels by the radical copolymerization of bifunctional diene monomers such as ethylene glycol disorbate and vinyl sorbate with oxygen .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] By incorporating a degradable linkage into gels, we can claim more variety of application of the gels as materials programmed for degradation after temporary use. The structural change and degradation of the network polymers are triggered by a stimulus such as heating, 1,[15][16][17][18][19] pH, 20,21 glucose, 22 antigen, 23 and enzymatic activities. 24 We recently reported that polyperoxide (PP), as a new kind of a degradable polymer, is readily produced by the radical copolymerization of 1,3-diene monomers with oxygen under mild conditions.…”
Section: Introductionmentioning
confidence: 99%